Bats! - Milton, Joyce; Moffatt, Judith (New York : scholastic, 1993)
Describes the physical characteristics, behavior, and habitats of different kinds of bats.
"Level 2, grades 1-3."
G3
Keywords: Bats -- Juvenile literature; Bats